POLITICAL RECRUITMENT OF CHINESE-INDONESIAN WOMEN CANDIDATE: STUDY OF PDI PERJUANGAN’S RECRUITMENT IN SEMARANG CITY LEGISLATIVE ELECTION 2014 - Sweinstani, Mouliza; Mariyah, Chusnul (PEOPLE: International Journal of Social Sciences, 2017)
This research aims to explain the dynamics of Chinese-Indonesian Women in their candidacy in local legislative elections in 2014 seen from the political recruitment conducted by PDI Perjuangan, the only party that can seat Chinese women candidate in DPRD Semarang City. Using qualitative methods by conducting in-depth interviews to PDI-Perjuangan elites in Semarang City and analyzing the result using political recruitment theory, Chinese-Indonesian Women's recruitment in PDI Perjuangan is based on party ideology that upholds diversity as well as the popular values and the role of the party elite as the gatekeeper that gives assessment of the resources offered by legislative candidates, where the decisive ones are the social resources, financial resources, and network resources. The author also found additional factors that Pippa Norris did not mention; those are cultural capital and relationships with male political elites. Besides, political recruitment conducted by PDI Perjuangan to Chinese-Indonesian Women Candidate was an open political recruitment, while usually it conducts the close mechanism one. Meanwhile, seen from the typology of recruitment according to Geddes, this recruitment is Immediate Survival typology that does not consider the competence of candidates and aims to foster good relations with the Chinese group in Semarang City. This recruitment is patronage and only takes into consideration to the candidate resources, especially financial and network resources (which is owned by the husband’s candidates). Therefore, the factors influencing the party recruiting Chinese-Indonesian Women in PDI Perjuangan Semarang are the political system of the country, the party’s internal democracy, and the candidate’s capitals including social capitals, network capitals, kinship with the elite, and one new capitals, culture, which are all supported by the candidate’s financial capital.